Answer:3x² - 9x - 12 =
3(x² - 3x - 4) =
3(x² + x - 4x - 4) =
3(x(x+1)-4(x+1)) =
3(x+1)(x-4)
Step-by-step explanation:
You find 8% of 55.35 which is 4.42
Then you find 15% of 55.35 which is 8.30
You add them together which equals 12.72
You then subtract 12.75 from 55.35 55.35-12.75=42.63
The original price was $42.63
Answer:
B
Step-by-step explanation:
A graph skewed right would have LESS dots on the right side
Hope this helped!
Answer:
hmm I'm not sure hold up give me a sec
Answer:
x = -2
Step-by-step explanation:
5x + 2(x - 4) = 5x + x - 10
First, we need to to multiply out the parathesis in the equation:
5x + 2(x - 4) = 5x + x - 10
5x + 2x - 8 = 5x + x - 10
Next, we can combine "like terms" to simplify the equation further:
5x + 2x - 8 = 5x + x - 10
7x - 8 = 6x - 10
Now we can isolate the variable "x" to one side:
7x - 8 = 6x - 10
x - 8 = -10
x = -2
To check our work, we can replace x with -2 in our original equation:
5x + 2(x - 4) = 5x + x - 10
5(-2) + 2 (-2 - 4) = 5(-2) + -2 - 10
-10 + 2 (-6) = -10 -2 - 10
-22 = -22
I hope this helps!
-TheBusinessMan